Availability and quality of anti-malarials among private sector outlets in Myanmar in 2012: results from a large, community-based, cross-sectional survey before a large-scale intervention - Khin, Hnin Su Su (Malar J, 2015)
BACKGROUND: Global malaria control efforts are threatened by the spread and emergence of artemisinin-resistant Plasmodium falciparum parasites. In 2012, the widespread sale of partial courses of artemisinin-based monotherapy was suspected to take place in the highly accessed, weakly regulated private sector in Myanmar, posing potentially major threats to drug resistance. This study investigated the presence of artemisinin-based monotherapies in the Myanmar private sector, particularly as partial courses of therapy, to inform the targeting of future interventions to stop artemisinin resistance. METHODS: A large cross-sectional survey comprised of a screening questionnaire was conducted across 26 townships in Myanmar between March and May, 2012. For outlets that stocked anti-malarials at the time of survey, a stock audit was conducted, and for outlets that stocked anti-malarials within 3 months of the survey, a provider survey was conducted. RESULTS: A total of 3,658 outlets were screened, 83% were retailers (pharmacies, itinerant drug vendors and general retailers) and 17% were healthcare providers (private facilities and health workers). Of the 3,658 outlets screened, 1,359 outlets (32%) stocked at least one anti-malarial at the time of study. Oral artemisinin-based monotherapy comprised of 33% of self-reported anti-malarials dispensing volumes found. The vast majority of artemisinin-based monotherapy was sold by retailers, where 63% confirmed that they sold partial courses of therapy by cutting blister packets. Very few retailers (5%) had malaria rapid diagnostic tests available, and quality-assured artemisinin-based combination therapy was virtually nonexistent among retailers. CONCLUSION: Informal private pharmacies, itinerant drug vendors and general retailers should be targeted for interventions to improve malaria treatment practices in Myanmar, particularly those that threaten the emergence and spread of artemisinin resistance.